Upgrading of K-feldspars of Samothraki island (NE Aegean Sea) igneous rocks for use in the ceramic and glass industry - VLAHOU, M.; CHRISTOFIDES, G.; SIKALIDIS, Κ.; KASSOLI-FOURNARAKI, A.; ELEFTHERIADIS, G. (Bulletin of the Geological Society of Greece, 2001)
K-feldspar phenocrysts from Samothraki island igneous rocks were upgraded by magnetic separation techniques and removal of mica, titanite and harmful oxides present as inclusions in the phenocrysts was achieved. Chemical analyses and technological tests were performed in order to compare free of inclusions and inclusion - bearing K-feldspar samples. Magnetic separation was proved adequate to upgrade the studied samples having particle size -0.5 to + 0.2 mm, resulting to high quality K-feldspars (Total alkalis> 15 wt%, Fe203 0.08 wt%, Ti02 0.04 wt%) suitable even for specific ceramic and glass products.